Synthesis, Quantum Chemical Computations And X-ray Crystallographic Studies Of A New Complex Based Of Manganese (+ii) - Benyza, N.; Messai, A.; Hamdaoui, A.; Lanez, T.; Sayin, K. (University of Eloued جامعة الوادي, 2017)
The ligand oxime, C7H9N5O2, was Synthesis and characterises with different characterization methods such as 1H NMR and FTIR spectroscopy. The complexation of this ligand with manganese (II) perchlorate yielded pink crystals of formula [Mn (C7H9N5O2)2]2+, 2[ClO4]-, which crystallized in the monoclinic space group P21/n with a = 12.824(3), b=13.799(2), c=15.441(4)Å, β = 100.17(2), and Z = 4. The complex consists of cations (+II) and two perchlorate anions, the cations part existing in a slightly distorted octahedral complex. Computational investigations of manganese (II) complex are done by using the DFTmethod with B3LYP functional in conjunction with the 6-31G(d,p) and lanl2dz basis sets in the gas phase imposing the C1 and C2v symmetries.
Articale in Journal of fundamental and Applied Sciences Vol. 09, N. 02
Keywords: Manganese complex; Crystal structure; DFT method; B3LYP functional; 6-31G(d,p) and (LANL2DZ) basis.